The Role of the Protocol Division in Supporting the Activities and Performance of Regional Leaders - Firhan Mahdavikia; Amirul Mustofa; Sarwani Sarwani; Dian Ferriswara (International Journal of Humanities and Social Sciences Reviews, 2026)
This study aims to analyze the role of the Protocol Division in supporting the activities and performance of regional leaders, particularly from the functional and interpersonal aspects in local government administration. The study employs a qualitative approach using Qualitative Secondary Analysis (QSA) through a review of literature, policy documents, and relevant previous research on protocol functions within government organizations. The analysis is grounded in organizational role theory and managerial role concepts. The results indicate that the Protocol Division plays a strategic role in supporting the effectiveness of regional leaders’ duties through two main dimensions. First, the functional role, which includes managing the regional leader’s activity agenda, organizing protocol-related events, arranging official ceremonies, and coordinating with regional apparatus and relevant institutions to ensure smooth implementation of government activities. Second, the interpersonal role, which encompasses acting as a communication liaison between the regional leader and various stakeholders, facilitating inter-agency working relationships, and supporting the representative function of the regional leader in official and community social events. The findings suggest that the successful execution of regional leaders’ activities is influenced not only by the leaders’ own leadership capacity but also by the effectiveness of organizational support from units that assist leadership, such as the Protocol Division. This role contributes to enhancing coordination effectiveness, ensuring smooth implementation of government activities, and strengthening the image and authority of regional leaders in performing their leadership functions. Therefore, strengthening institutional capacity, improving human resource competencies, and utilizing information technology in managing leadership activities are crucial factors in optimizing the role of the Protocol Division in local governance.